Analytical study of flexible stimulation waveforms in muscle fatigue reduction - E. Noorsal; S. Z. Yahaya; Z. Hussain; R. Boudville; M. N. Ibrahim; Y. Mohd Ali (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper presents the analytical study of flexible stimulation waveforms in muscle fatigue reduction for functional electrical stimulator (FES)-assisted hemiplegic muscle activities. The major challenge of muscle contraction induced by FES is early muscle fatigue which greatly limits activities such as FES-assisted standing and walking. The fixed stimulation pattern applied on a same motor unit has resulted the motor unit to be overworked and fatigue easily. Therefore, in this work, the stimulus parameters, which include the pulse width duration and the frequency were varied to create a few flexible stimulation waveforms using MATLAB/Simulink. The pulse width duration was modulated from 100µs – 500µs to generate five types of flexible stimulation waveforms such as Rectangular, Trapezoidal, Ramp Up, Ramp Down and Triangular. Concurrently, a few ranges of stimulus frequency were also used, which include 20Hz, 30Hz and 50Hz. The generated flexible stimulation waveforms were applied onto a humanoid muscle model to investigate and analyse the muscle output response and early muscle fatigue reduction. From the conducted simulation results and analyses, it was observed that flexible stimulation waveforms such as Triangular, Ramp Up and Ramp Down could reduce early muscle fatigue phenomenon by having lower average of negative slope, in the range of 0.012 to 0.013 for the muscle fitness. In contrast, the Rectangular and Trapezoidal shapes were found to have higher negative slope of muscle fitness in the range of 0.028 to 0.031. The Ramp Down shape was found to have the lowest average of negative slope (0.012) while Rectangular was found to have the highest average of negative slope (0.031). Therefore, it can be concluded that flexible stimulation waveforms such Ramp Down, Ramp Up and Triangular shapes could reduce early muscle fatigue phenomenon with Ramp Down shape having the highest muscle fatigue reduction.